Left ventricular hypertrophy in young hypertensives: the possible crosstalk of mTOR and angiotensin-II -a case-control study - Busayo Onafowoke Oguntola; Stephen Olawale Oguntola; Opeyemi Ezekiel Ojo; Pauleen Ayomide Ukpabio; Adams Olalekan Omoaghe; Kehinde Samuel Olaniyi (BMC Cardiovascular Disorders)
Abstract Background Hypertension is a major cause of cardiac dysfunction. The earliest manifestation is left ventricular remodeling/hypertrophy. The occurrence of adverse cardiac remodeling and outcomes occurs irrespective of age in blacks. This necessitated an estimate of the prevalence of left ventricular hypertrophy (LVH) and an assessment of the roles of the mammalian target organ of rapamycin (mTOR) and angiotensin-II (Ang II) as possible pathogenic markers of LVH among young hypertensives. Methods This prospective case-control study involved 110 hypertensive and 60 normotensive (control) participants aged 18–45 across tertiary hospitals in Ekiti state. Ethical approval was obtained from all the various institutions. Participants were recruited consecutively after giving informed consent. Sociodemographic/clinical information, resting electrocardiogram and echocardiography were obtained. Venous blood was obtained to estimate mTOR, Ang II, Chemerin, lipids – triglyceride (TG), high-density lipoprotein (HDL), total cholesterol (TC), troponin-T, NF-Kβ, and Galectin-3 using enzyme-linked immunosorbent assay. Results The prevalence of LVH among the hypertensive group was 20.9%, 39%, 11.01%, and 15.74% using 2D-transthoracic echocardiography, Sokolow-Lyon, Cornell’s and Cornell product ECG criteria. Also, hypertensives with LVH had a significantly increased blood pressure, body mass index, serum level of TG, TG/HDL, TC/HDL, chemerin, troponin T, Galectin-3 and total mTOR compared to normotensive and hypertensives without LVH. At the same time, serum NF-kβ and Ang II were only significant when compared with normotensive but not hypertensives without LVH. The total mTOR moderately correlated positively with ANG-II. Conclusions The results suggest an interaction between mTOR and Ang II in the development of LVH. In addition, it shows that LVH is associated with dyslipidemia, inflammation, and fibrosis.